Towards Semantic Fusion using Information Quality Awareness to Support Emergency Situation Assessment - Pereira Junior, Valdir Amancio; Sanches, Mathues Ferraroni; Botega, Leonardo Castro; Coneglian, Caio Saraiva [UNESP]; Rocha, A.; Correia, A. M.; Adeli, H.; Reis, L. P.; Teixeira, M. M. (Springer, 2016)
Information Fusion is the integration of synergic information to support high-level decision-making. Emergency management systems are applications that may take advantage of such integration by supporting system's operators on developing situation awareness (SAW) and dealing with the critical and dynamic nature of real emergency scenarios. Semantic models help to describe and to determine synergy among entities that may be useful for fusion and situation assessment routines (SA). In this context, the awareness of information quality issues can enrich even more the knowledge that humans and system hold about situations. The objective of this paper is to present advances towards a new semantic fusion approach supported by information quality inferences and semantic web concepts to improve the assessments about emergency situations and hence supporting situation awareness. A previous fusion approach based on a syntactic integration with quality indexes is used to illustrate the improvements on information fusion results with the semantic models.
Keywords: Semantic Fusion; Information Fusion; Situation Awareness; Situation Assessment; Emergency Management Systems; Information Quality